New Screen-Printed Carbon Electrodes Molecularly Modified with Methylphenidate Film for Electrochemical Determination of Dopamine by Linear Scan Voltammetry - Segura-Segura, R; Segura-Segura, R; Penagos-Llanos, J; Penagos-Llanos, J (John Wiley and Sons Inc, 2025)
The development of new sensors for dopamine (DP) detection is crucial due to its role as one of the most important neurotransmitters for maintaining mental health. In this context, a novel and simple 2D screen-printed carbon electrode (SPCE) molecularly modified electrode with a methylphenidate film was developed. This electrode exhibited notable activity in DP oxidation at potential values below 0.3 V, achieving a 300% increase in anodic current compared to the unmodified SPCE in an acidic environment (pH 3.0) with phosphate buffer solution. Cyclic voltammetry and electrochemical impedance spectroscopy were used to characterize the electrode s electrochemical behavior. The electrode achieved a DP detection limit of 0.15 µmol/L using linear scan voltammetry. Interference studies with ascorbic acid and uric acid confirmed the electrode s selectivity for DP detection. The sensor s effectiveness was validated using real human urine samples, demonstrating accurate and reliable performance. © 2025 Wiley-VCH GmbH.